ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN BERBASIS BAGI HASIL PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2010-2015 - Diah Ayu Kustariyanti, 13.05.52.0061; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2017)
The sudy examines the effect of the level revenue sharing, non-performing finance, equity, third party funds, and capital adequacy ratio based on the financing for the resultson Islamic banks in Indonesia. This study examines used a sample of 56 Islamic banks in Indonesia premises-year study from 2010 to 2015. The data sources get from annual reports throughout the Islamic banks. The result showed that the equity and deposits significant positive effect on the results-based financing. The level of profit sharing and capital adequacy ratio significantly negative influence.whereas for non perfoming finance does not influence the results-based financing.Keywords: Finance Profit Sharing Level Profit Sharing, Non-Performing Finance, Equity, Deposits, And Capital Adequacy Ratio